2019
DOI: 10.1177/2050312119852527
|View full text |Cite
|
Sign up to set email alerts
|

Somatic health and its association with negative psychosocial factors in a sample of Moroccan adolescents

Abstract: Background: Adolescence is a distinct developmental phase characterized by multiple physical and psychological changes and by an increased vulnerability to somatic and mental health problems. These risk and vulnerability factors are part of a complex biopsychosocial matrix, encompassing multiple factors, such as inherited biological determinants and psychological, societal, and cultural influences, which affect an adolescent’s overall wellbeing. In Morocco, similar to other developing countries, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 75 publications
1
15
1
1
Order By: Relevance
“…About 50% of the Swedish high school students reported one or several somatic complaints, a similar prevalence to what was found in a large-scale nation-wide Swedish study [55]. There were no gender differences in the number of reported somatic complaints, a result that may contradict previous observations, where female adolescents reported more somatic complaints [6,7,55]. The most prevalent somatic complaint was allergy (found in more than one-third of the study population), followed by migraine and asthma (reported by about 15% of the study population).…”
Section: Somatic Complainssupporting
confidence: 72%
See 2 more Smart Citations
“…About 50% of the Swedish high school students reported one or several somatic complaints, a similar prevalence to what was found in a large-scale nation-wide Swedish study [55]. There were no gender differences in the number of reported somatic complaints, a result that may contradict previous observations, where female adolescents reported more somatic complaints [6,7,55]. The most prevalent somatic complaint was allergy (found in more than one-third of the study population), followed by migraine and asthma (reported by about 15% of the study population).…”
Section: Somatic Complainssupporting
confidence: 72%
“…Approximately 50% of them reported the experience of both physical and psychological abuse. In comparison, the prevalence of physical and psychological abuse reported by the adolescent student sample in the Moroccan study [7,11,13] were 17% of the females and 13% of the males. We hypothesize, that this significant discrepancy can be explained not only by cultural differences (between Sweden and Morocco) but also by a difference in time between the two data collections.…”
Section: Negative Psychosocial Environmental Factors and Adolescent Mmentioning
confidence: 85%
See 1 more Smart Citation
“…The Global Burden of Disease study reported that, from 1980 to 2016, diarrhea was the eighth leading cause of death worldwide, with more than 16.5 million deaths every year [4]. One third of adolescents suffer from diarrhea in developing countries [5] and a study found that fever and diarrhea often appear together in patients [6]. Fever was the most common symptom of health care needs in the tropics and low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have considered Moroccan adolescents have focused on immigrants living in other, mainly European countries ( Curtis et al, 2018 ), but recently, Morocco has displayed an interest in using the education system to enhance its development ( World Bank Group, 2019 ), prompting growth in efforts to analyze which areas should be focused on. These areas include physical and mental health, emphasizing medical models (i.e., Zouini et al, 2019a , b ), and psychosocial aspects [i.e., social support or emotional intelligence (EI); Lopez-Zafra et al, 2019 ]. However, the interplay between these psychosocial (socioemotional) aspects and academic adjustment still needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%